Autopsy Diagnosis of a Rare Case of Near-Drowning (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The term near-drowning is commonly used for the victim who almost survives after an incidence of aspiration of fluid, but dies later due to complications of drowning. Drowning is one of the common causes of unnatural deaths in India, but the reporting of cases of near-drowning is rare. In the present case, dead body of a 1-year-old male child was brought to us for autopsy examination with a history of rescue from accidental drowning in a water tank at home. The victim was admitted in hospital before death for a few hours, where he was resuscitated but could not survive due to difficulty in respiration followed by irretrievable cardiac arrest. Detection of the cause of death in such cases is a difficult task for the autopsy surgeon, especially, in the absence of typical findings of ante mortem drowning, which is frequently present in such cases. Absence of theses ante-mortem features of drowning might be due to the measures used in the treatment of the victim and that is why it is always better to correlate the autopsy findings with the history and clinical record, which can help us to understand the reasons of negative findings in a case of near-drowning. This case is presented here to discuss its different medico-legal aspects as it is rare of its kind.
Keywords: Drowning; Near-drowning; Accident; Autopsy